Alkaline‐Earth Metal Ca and N Codoped TiO2 with Exposed {001} Facets for Enhancing Visible Light Photocatalytic Activity. Issue 8 (30th April 2014) - Zhang, Jun; Qian, Lisha; Fu, Wei; Xi, Junhua; Ji, Zhenguo; Hintzen, B.
<x xml:space="preserve">Abstract</x> Alkaline‐earth metal Ca and N codoped TiO2 sheets with exposed {001} facets were obtained through a one‐step hydrothermal process. The codoped TiO2 appears as microsheets with length of 1–2 μm and thickness of 100–200 nm. The X‐ray diffractometer and X‐ray photoelectron spectroscopy results confirm that Ca and N codoped TiO2 has higher crystallinity than N‐doped TiO2, as well Ca, N atoms were successfully codoped into TiO2 as interstitial Ca and interstitial N or an O–Ti–N structure, respectively. Compared with N monodoped, further alkaline‐earth Ca codoped has little influence on the energy bands of TiO2 except slightly elevating the conduction band edge at a value of 0.02 eV. The hydroxyl radicals (OH) producing and photocatalytic experiment shows that Ca and N codoped can effectively decrease the generation of recombination centers, and enhance separation efficiency of photo‐induced electrons and holes as well as the photocatalytic activity of TiO2. The codoped photocatalyst has the highest photocatalytic activity when Ca doped ratio reach 0.48%. Excess Ca doped will weaken the crystallization of anatase TiO2, form charge center, produce new recombination centers and finally reduce the photocatalytic activity of TiO2.